2008
DOI: 10.1073/pnas.0801180105
|View full text |Cite
|
Sign up to set email alerts
|

H elimination and metastable lifetimes in the UV photoexcitation of diacetylene

Abstract: We present an experimental investigation of the UV photochemistry of diacetylene under collisionless conditions. The H loss channel is studied using DC slice ion imaging with two-color reduced-Doppler detection at 243 nm and 212 nm. The photochemistry is further studied deep in the vacuum UV, that is, at Lymanalpha (121.6 nm). Translational energy distributions for the H ؉ C 4H product arising from dissociation of C 4H2 after excitation at 243, 212, and 121.6 nm show an isotropic angular distribution and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…The characteristic translational energy profile, with the peak at about 2000 cm −1 and extending to the energetic limit, is quite similar to that observed in 121.6 photolysis of C 4 H 2 reported by Suits and co-workers. 8 This suggests the statistical component should come from the dissociation process on the ground state following IC from initially excited Rydberg state to the ground state S 0 . Such dissociation time is long enough to allow for complete internal energy randomization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristic translational energy profile, with the peak at about 2000 cm −1 and extending to the energetic limit, is quite similar to that observed in 121.6 photolysis of C 4 H 2 reported by Suits and co-workers. 8 This suggests the statistical component should come from the dissociation process on the ground state following IC from initially excited Rydberg state to the ground state S 0 . Such dissociation time is long enough to allow for complete internal energy randomization.…”
Section: Resultsmentioning
confidence: 99%
“…However, the recently observed submicron-second lifetimes suggested that reactions of metastable C 4 H 2 are likely to be less important in Titan's atmosphere than previously believed. 8 The second spectrum region, between 115 and 175 nm, shows a succession of several strong absorption features, which belong to the R and R Rydberg series. For example, an intense peak observed at 164.4 nm has been assigned by Smith et al to the R 1 u ← 1 g + transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions involving metastable C4H2* molecules formed by such photoexcitation were touted as a possible route to forming the larger polyynes and polycyclic aromatic hydrocarbons that contribute to the haze that cloaks Titan, 30 but such a view was challenged following later measurements that showed that these C4H2* states have sub-s lifetimes. 31 The TKER spectra of the H + C4H products formed when exciting C4H2 at shorter wavelengths (in the range 127.5    164.4 nm) chosen to match with resolved Rydberg features in the parent absorption spectrum show peaks sitting on a continuous background. 32,33 Such structure reflects the formation of excited C4H(A 2 ) state radicals, with specific vibrational excitation in the CCC bend and CC stretch modes.…”
Section: Acetylene Higher Alkynes Alkyl Analogues and Nitrilesmentioning
confidence: 99%
“…Again, the interaction of multiple potential energy surfaces, including the formation of conical intersections, is an essential feature of the system. A study of the photodissociation of diacetylene uses several excitation wavelengths, including one deep in the UV region, and observes the recoiling hydrogen atoms with ion imaging (12).…”
mentioning
confidence: 99%